The Internal Organs Weight of 6-Weeks Old Native Chickens after Supplement Addition With L-threonine and L-tryptophan in the Feed - Lisnahan, Charles Venirius; Nahak, Oktavianus Rafael (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2019)
The aim of this experiment was to identify the internal organs weight of 6-weeks old native chickens after treatment feed with l-threonine and l-tryptophan supplement. This experimental research used 128 native chickens aged one-week-old in a Completely Randomized Design with four treatments and four replications. The dietary treatments were T0 (control feed), T1 (T0 + 0.35% l-threonine + 0.10% l-tryptophan), T2 (T0 + 0.68% l-threonine + 0.17% l-tryptophan), and T3 (T0 + 1.00% l-threonine + 0.25% l-tryptophan). The variables measured included body weight, liver weight, pancreas weight, gizzard weight, and intestinal length. Statistical analysis showed that l-threonine and l-tryptophan significantly affected body weight, liver weight, pancreas weight, gizzard weight and intestinal length. Supplementing 1.00% l-threonine and 0.25% l- tryptophan to feed contributed to the highest body weight and internal organs weight of native chickens.